Dual Three-level-grid-converter Control Strategy of AC-DC-ACMain Drive System for Rolling Mill - CHEN Tao; ZHANG Zhixue (Kongzhi Yu Xinxi Jishu)
Medium voltage three-level converters are widely used in the field of industrial drive systems. In some super-power occasions, it is very important to reduce the harmonics at grid side by using multiple rectifying applications. In this paper, the principle of harmonic optimal realization of a series winding transformer on the primary side was analyzed, and a harmonic optimal control strategy of dual-grid-converter based on single current closed-loop and a comprehensive compensation method for DC bias of transformer were proposed. The experimental results show that the proposed control strategy can reduce the converter input current harmonics significantly.